Analysis of Students' Physical Condition in Extracurricular Football - Sumantri, Ajis; Personi, Megi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This study aims to determine the analysis of students' Physical Conditions in Extracurricular Football students at SMP N 11 Kota Bengkulu. This study used quantitative descriptive research, with a type of survey method. The sample in this study amounted to 20 participants of Extracurricular Football at SMP N 11 Kota Bengkulu. The data collection technique in this study used tests and measurements.   Based on the results of research that has been done, it can be explained that: 1) Have a physical condition in the moderate category (9 people or 45%). 2) Student strength through push ups in the less category (8 people (40%). 3) Agility of students in the medium category (10 people or 50%). 4) Flexibility of students in the medium category (10 people or 50%). 5) Explosive Power of students in the medium category (8 people or 40%). 6) The balance of students in the less category (9 people or 45%). 7) The speed of students in the medium category (9 people 45%). Based on these data, it can be concluded that in general the physical condition of students is in the "medium" category.